Transcription levels of sirtuin family in neural stem cells and brain tissues of adult mice - Wang, H. F.; Li, Q.; Feng, R. L.; Wen, T. Q. (Cellular and Molecular Biology, 2012)
Neural stem cells (NSCs) has been used as a well-known model to investigate apoptosis, differentiation, maintenance of stem cells status, and therapy of neurological disease. The C17.2 NSCs line was produced after v-myc transformation of neural progenitor from mouse cerebellar cortex. Sirtuin family plays important roles involved in neuronal differentiation, genomic stability, lifespan, cell survival. However, little is known about gene expression variation of sirtuin family in C17.2 NSCs, primary NSCs, and different brain tissues in adult mice. Here, we confirmed that the mRNA expression levels of sirt2, 3, 4, 5, and 7 in E14.5 NSCs were significantly higher than in C17.2 NSCs, whereas that sirt 6 displayed an opposing mode. Moreover, a higher mRNA level of sirtuin family was observed in the adult mouse brain compared to C17.2 NSCs. In addition, histone deacetylase (HDAC) inhibitors nicotinamide and Trichostatin A (TSA) were used to explore differential changes at the transcriptional level of sirtuins. Results indicated that the expression of sirt1, sirt5 and sirt6 was significant downregulated by nicotinamide treatment. Whereas, a significant downregulation in sirt1 and sirt3 and a significant upregulation in sirt2, sirt4, sirt6, and sirt7 were observed in the treatment of TSA. Thus our studies indicate different sirtuin mRNA expression profiles between C17.2 NSCs, E14.5 NSCs and brain tissues, suggesting the transcriptional regulation of sirtuin family could be mediated by different histone acetylation.